XPRIZE Carbon Removal: largest incentive prize in history. Issue 3 (9th September 2021) - Extavour, Marcius
Abstract : XPRIZE Carbon Removal is a 4-year global competition that invites innovators and teams from anywhere on the planet to create and demonstrate solutions that can pull carbon dioxide directly from the atmosphere or oceans, and sequester it.